Legal Protection of Musical Royalty Rights in the Digital Era: Challenges and Solutions - Nasirun, Indrasatya Octavianus (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
This study aims to analyze the challenges and solutions in the legal protection of music royalties in the digital era identify systemic problems in the existing legal framework and royalty distribution system and explore the potential of emerging technologies as alternative solutions The research method uses a qualitative approach with a systematic literature review of relevant academic publications legal documents and industry reports analyzed using thematic content analysis and comparative analysis techniques to identify key patterns and themes The results of the study reveal three main findings: first legal challenges include the complexity of cross border jurisdictions weaknesses in enforcement mechanisms and ambiguity in the classification of digital music use which create regulatory gaps; second the digital royalty distribution system suffers from problems of lack of transparency unfairness of the pro rata model complexity of the distribution chain and the phenomenon of unclaimed royalties which is detrimental to music creators; third blockchain technology artificial intelligence and tokenization offer potential solutions through smart contracts automated content identification and user centric payment systems The study concludes that comprehensive reforms are needed that integrate international regulatory harmonization transformation of the royalty distribution system and the implementation of advanced technology to create effective transparent and fair digital music royalty protection for all stakeholders in the global music industry < p>